2002
DOI: 10.1002/gps.714
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 and testosterone interact in the risk of Alzheimer's disease in men

Abstract: Objectives To assess the association between testosterone levels and APOEε4 in cases with AD and controls. Method We included 61 men with definite or probable Alzheimer's disease (AD) and 55 elderly male controls from the Oxford Project to Investigate Memory and Ageing (OPTIMA). Testosterone was measured using a competitive enzyme immunoassay (Bayer®). Results We found that both low serum testosterone and the interaction between testosterone and APOEε4 were associated with AD. Furthermore, testosterone levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 4 publications
1
52
1
Order By: Relevance
“…In addition, having the APOE epsilon 4 allele, a well established genetic risk factor for AD, was seen to be associated with lower TT, also in control men of the OPTIMA case control cohort who had not (yet?) developed dementia symptoms 61 . It may thus be the case that men at risk for AD have genetic polymorphisms that predispose them to accelerated age-related lowering of TT levels and an increased conversion of TT into estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, having the APOE epsilon 4 allele, a well established genetic risk factor for AD, was seen to be associated with lower TT, also in control men of the OPTIMA case control cohort who had not (yet?) developed dementia symptoms 61 . It may thus be the case that men at risk for AD have genetic polymorphisms that predispose them to accelerated age-related lowering of TT levels and an increased conversion of TT into estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, traditional risk factors for stroke have been linked with AD, [35][36][37][38] and vascular risk factors such as hyperhomocysteinemia, atherosclerosis, hyperlipidemia, hypercholesterolemia, and the presence of the APOE-4 or APOE-2 alleles are often seen in individuals with LA. 39 -42 Also, as compared with clinicbased autopsy studies, population-based autopsy studies now suggest that the incidence of "pure" AD is often well below 50%.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the initial studies, Hogervorst and colleagues (2001) reported significantly reduced serum levels of testosterone from men with AD in comparison to age-matched, non-demented men. In subsequent studies by this group, both total (Hogervorst et al, 2004;Hogervorst et al, 2003;Lehmann et al, 2004) and free (Hogervorst et al, 2002) testosterone levels were found to be significantly lower in men without AD irrespective of potentially confounding such indices as age, education, body mass index, smoking, alcohol use, diabetes, and hormone therapy. Similar findings of low testosterone in men with AD have been reported in several (Almeida et al, 2004;Moffat et al, 2004;Paoletti et al, 2004;Rasmuson et al, 2002;Watanabe et al, 2004) but not all (Pennanen et al, 2004) studies.…”
Section: Age-related Androgen Depletion and Alzheimer's Diseasementioning
confidence: 93%